2018
DOI: 10.3389/fphys.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Modulation of Cultured Primary Human Aortic Vascular Smooth Muscle Cells by Uremic Serum

Abstract: Patients with chronic kidney disease (CKD) have a markedly increased incidence of cardiovascular disease (CVD). The high concentration of circulating uremic toxins and alterations in mineral metabolism and hormone levels produce vascular wall remodeling and significant vascular damage. Medial calcification is an early vascular event in CKD patients and is associated to apoptosis or necrosis and trans-differentiation of vascular smooth muscle cells (VSMC) to an osteogenic phenotype. VSMC obtained from bovine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 45 publications
(59 reference statements)
2
42
0
Order By: Relevance
“…The apoptosis of VSMCs promotes atherogenesis, various aspects of plaque instability, intimal calcification, and medial calcification [ 58 , 59 ]. Vessels from pediatric patients on dialysis display extensive VSMC apoptosis [ 60 ], and uremic serum promotes the extensive apoptosis of human VSMCs cultured in vitro [ 9 ]. The apoptotic bodies derived from these VSMCs are known to act as nucleating structures for calcium crystals [ 59 ], and thus promote vascular calcification.…”
Section: The Impact Of Uremic Toxins On Vsmc Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apoptosis of VSMCs promotes atherogenesis, various aspects of plaque instability, intimal calcification, and medial calcification [ 58 , 59 ]. Vessels from pediatric patients on dialysis display extensive VSMC apoptosis [ 60 ], and uremic serum promotes the extensive apoptosis of human VSMCs cultured in vitro [ 9 ]. The apoptotic bodies derived from these VSMCs are known to act as nucleating structures for calcium crystals [ 59 ], and thus promote vascular calcification.…”
Section: The Impact Of Uremic Toxins On Vsmc Functionmentioning
confidence: 99%
“…Indeed, PCS significantly increased the percentage of apoptotic VSMCs in vitro through upregulation of Bax and downregulation of Bcl-2 [ 22 ]. In vitro, high-Pi-induced human VSMC apoptosis (as evidenced by changes in nuclear shape and phosphatidyl-serine externalization) is associated with the increased expression of pro-apoptotic BCL2 family proteins and caspase-3—suggesting a role for the intrinsic pathway [ 9 , 40 ]. These data were confirmed by the observation that high-Pi-induced downregulation of the anti-apoptotic growth-arrest-specific gene 6 and its receptor Axl induced VSMC apoptosis via increased caspase 3 activation [ 62 ].…”
Section: The Impact Of Uremic Toxins On Vsmc Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data showed that neither high-TyG index nor FPG was an independent risk factor of SFA calcification, it indicated that under impaired kidney function condition, hyperglycemia may accelerate the development of SFA calcification. It was supported by the fact that the induction of in vitro T2DM calcification model required the high phosphate microenvironment (mimicked the reduced eGFR) [30][31][32]. Vascular calcification was thought to be a manifestation of vascular aging [33].…”
Section: Discussionmentioning
confidence: 99%
“…Osteo-chondrogenesis and VC are driven by stressors including high phosphate, high calcium, oxidative stress, inflammation, senescence, apoptosis and alkalinization [ 21 , 22 ], all (except alkalinization) common manifestations of uraemia. Thus, non-surprisingly, uremic serum accelerates VC in VSMC in vitro [ 23 , 24 , 25 ].…”
Section: Vascular Calcificationmentioning
confidence: 99%